2020
DOI: 10.1111/jocn.15506
|View full text |Cite
|
Sign up to set email alerts
|

Prioritisation of diabetes‐related footcare amongst primary care healthcare professionals

Abstract: Aims and objectives: To assess primary healthcare professionals' priority for managing diabetic foot disease (DFD) over the progressive course of the condition compared to other aspects of diabetes care. Background: DFD affects up to 60 million people globally. Evidence suggests that comprehensive preventative footcare may reduce serious complications of DFD, such as amputation. Design: A cross-sectional quantitative study reported according to STROBE statement. Methods: General Practitioners (GPs) and Credent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…These results emphasize the importance for clinicians to prioritize preventative foot care at an earlier stage in the diabetes care continuum. Additionally, the findings underscore the significance of proactive foot care practices over reactive ones, as such prioritization is crucial in preventing foot ulcers and the subsequent need for amputation [ 16 ]. Furthermore, binary logistic regression analysis revealed that healthcare professionals within the age range of 35-44 years, with 5-10 years of experience, employed at private hospitals, managing a higher number of practice clinics per week, and treating a greater number of patients with diabetes in each clinic, exhibited a greater likelihood of prioritizing foot care in their clinical practices.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These results emphasize the importance for clinicians to prioritize preventative foot care at an earlier stage in the diabetes care continuum. Additionally, the findings underscore the significance of proactive foot care practices over reactive ones, as such prioritization is crucial in preventing foot ulcers and the subsequent need for amputation [ 16 ]. Furthermore, binary logistic regression analysis revealed that healthcare professionals within the age range of 35-44 years, with 5-10 years of experience, employed at private hospitals, managing a higher number of practice clinics per week, and treating a greater number of patients with diabetes in each clinic, exhibited a greater likelihood of prioritizing foot care in their clinical practices.…”
Section: Discussionmentioning
confidence: 99%
“…This study used an online survey that Mullan et al [ 16 ] had previously validated in a cross-sectional study they conducted in Australia. The questionnaire was constructed on Google Form® and then distributed via online platforms to the targeted population of the study (inclusion criteria below) using a convenience sampling technique.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is a centralised model of care, as the MDT provides integrated diabetes care in one place. 90 This is considered to be the gold standard of care due to the complex needs of patients with DFD and in terms of how podiatry services are delivered 91,92 as it is seen as the most effective method of delivering podiatry care in diabetes care settings. 93 ‘Where we work here we have team of clinicians, we had this team before we had our actual more targeted multidisciplinary team.’ (Betsy) ‘I am really lucky to be a part of an awesome interdisciplinary team.’ (Aroha) ‘I feel lucky that we’re in a multidisciplinary setting because if you’re in isolation you’d be very limited in what you could do.’ (Drew) ‘Also, the diabetes team we do work with.…”
Section: Methodsmentioning
confidence: 99%
“…This is a centralised model of care, as the MDT provides integrated diabetes care in one place. 90 This is considered to be the gold standard of care due to the complex needs of patients with DFD and in terms of how podiatry services are delivered 91,92 as it is seen as the most effective method of delivering podiatry care in diabetes care settings. 93 'Where we work here we have team of clinicians, we had this team before we had our actual more targeted multidisciplinary team.'…”
Section: Superordinate Theme 3: Best Outcomesmentioning
confidence: 99%